1988
DOI: 10.1093/bja/61.6.675
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Myocardial Ischaemia During Anaesthesia in Treated and Untreated Hypertensive Patients

Abstract: Hypertensive patients were monitored for myocardial ischaemia during anaesthesia and surgery with the V5 lead of a standard electrocardiograph. Myocardial ischaemia was detected in 11 of 39 untreated hypertensive patients and in four of seven receiving therapy with a diuretic, but in none of 44 receiving atenolol. Fourteen of the atenolol-treated patients were receiving the drug on a long-term basis and the remaining 30 were treated acutely only on the morning of surgery. When myocardial ischaemia was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(72 citation statements)
references
References 8 publications
0
67
1
4
Order By: Relevance
“…23,26,29,30,33,35,38,39,48 Heart rate achieved was not significant for any of the efficacy outcomes apart from non-fatal myocardial infarction-trials that achieved heart rate of 75 beats per min or less reported a lower reduction in risk than did the other group (tables 2 and 3).…”
Section: Weight (%)mentioning
confidence: 96%
See 4 more Smart Citations
“…23,26,29,30,33,35,38,39,48 Heart rate achieved was not significant for any of the efficacy outcomes apart from non-fatal myocardial infarction-trials that achieved heart rate of 75 beats per min or less reported a lower reduction in risk than did the other group (tables 2 and 3).…”
Section: Weight (%)mentioning
confidence: 96%
“…High-bias risk trials POBBLE 3 Poldermans 32 Jakobsen 46 Jakobsen 34 Lai 35 Magnusson 37 Magnusson 50 Stone 38 Urban 39 Zaugg 3 Poldermans 32 Jakobsen 46 Lai 35 Magnusson 37 Magnusson 50 Miller 40 Stone 38 Urban 39 Zaugg High-bias risk trials Jakobsen 426 Lai 35 Liu 36 Magnusson 50 POBBLE 3 Poldermans 32 Urban 39 Zaugg 33 Jakobsen 46 Stone …”
Section: Graph Marks Arrowsmentioning
confidence: 99%
See 3 more Smart Citations